Characteristics and immune functions of the endogenous CRISPR-Cas systems in myxobacteria - Hu, Wei-feng; Yang, Jiang-yu; Wang, Jing-jing; Yuan, Shu-fei; Yue, Xin-jing; Zhang, Zheng; Zhang, Ya-qi; Meng, Jun-yan; Li, Yue-zhong (mSystems, 2024)
Serving as an adaptive immune system, clustered regularly interspaced short palindromic repeats and their associated proteins (CRISPR-Cas) empower prokaryotes to fend off the intrusion of external genetic materials. Myxobacteria are a collective of swarming Gram-stain-negative predatory bacteria distinguished by intricate multicellular social behavior. An in-depth analysis of their intrinsic CRISPR-Cas systems is beneficial for our understanding of the survival strategies employed by host cells within their environmental niches. Moreover, the experimental findings presented in this study not only suggest the robust immune functions of CRISPR-Cas in myxobacteria but also their potential applications.